2013
DOI: 10.1080/07391102.2013.855142
|View full text |Cite
|
Sign up to set email alerts
|

Interface dynamics explain assembly dependency of influenza neuraminidase catalytic activity

Abstract: Influenza virus neuraminidase (iNA) is a homotetrameric surface protein of the influenza virus and an established target for antiviral drugs. In contrast to neuraminidases (NAs) of other biological systems (non-iNAs), enzymatic activity of iNA is only observed in a quaternary assembly and iNA needs the tetramerization to mediate enzymatic activity. Obviously, differences on a molecular level between iNA and non-iNAs are responsible for this intriguing observation. Comparison between protein structures and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The expression of NA in the native conformation is believed to be crucial for the induction of anti-NA antibodies with inhibitory activity (62). As only the native tetrameric NA is enzymatically active (63,64), sialidase activity is regarded as an indicator of NA immunogenicity (62). In contrast to vaccination with VRPs, intramuscular immunization of chickens with inactivated influenza virus resulted in significantly lower titers of anti-NA antibodies, although relatively high anti-HA titers were induced.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NA in the native conformation is believed to be crucial for the induction of anti-NA antibodies with inhibitory activity (62). As only the native tetrameric NA is enzymatically active (63,64), sialidase activity is regarded as an indicator of NA immunogenicity (62). In contrast to vaccination with VRPs, intramuscular immunization of chickens with inactivated influenza virus resulted in significantly lower titers of anti-NA antibodies, although relatively high anti-HA titers were induced.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme regulation involving changes in assembly state has already been established for several enzymatic systems including influenza neuraminidase. Molecular dynamics simulations were found to be helpful in the characterization of the changes in the system's dynamics after the formation of additional macromolecular interfaces by tetramerization [70].…”
Section: A Dynamic View Of Pah Regulationmentioning
confidence: 99%
“…From the pair of interactions present in most of the apo and holo tetrameric closed‐ and open‐loop, it is observed that five pairs of polar interactions: Arg107.NH1(chain A)–Gln.O136(chain C), Ser110.OG(chain A)–Asp142.OD1(chain C), Tyr169.OH(chain A)–Asp113.N(chain D), Asp113.N(chain B)–Tyr169.OH(chain D) and Tyr169.OH(chain B)–Asp113.N(chain C), and three pair of hydrophobic interactions: Ile108.CD1(chain A)–Phe115.CE2(chain C), Ile108.CG1(chain A)–Leu139.CD1(chain C) and Trp458.CD1(chain A)–Val176.CG1(chain C) are present in most complexes. From these pairs of interactions, Arg107.NH1(chain A)–Gln.O136(chain C) and Ser110.OG(chain A)–Asp142.OD1(C) have also been observed for other tetramers of subtype N1 (avian 2004, pandemic 1918, and pandemic 2009 influenza NA) through MD simulations . These interactions are localized between the α‐helix around S105‐S110 and the 150‐loop (135‐155), from which two residues (Arg151 and Arg152) are present in the 150‐loop and participate in oseltamivir or sialic acid stabilization (Figures ); therefore, differences in the energetic state of this interaction together with the other seven protein‐protein interactions may impact the affinity of ligands in the active site of tetrameric NA.…”
Section: Resultsmentioning
confidence: 61%
“…Recently, von Grafensteina et al . revealed that the altered dynamics of the 150‐loop depend on the assembly state . The tetrameric open‐loop and closed‐loop NA in the free and bound state was used to show how the conformational differences in the loop and apo and bound state impact the map of interaction on a tetrameric system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation